What do we know about the future of food systems in South Asia? - Nedumaran, Swamikannu; Thomas, Judy; Nandi, Ravi; Padmanabhan, Jyosthnaa; Afari-Sefa, Victor (International Food Policy Research Institute, 2025)
Micronutrient availability in South Asia is projected to increase by 46 percent by 2050, reflecting a significant transition from traditional cereal-based diets to diverse, nutrient-rich foods, though affordability limits access for low-income groups.